Religion and politics beyond the culture wars new directions in a divided America - Dochuk, Darren (University of Notre Dame Press, 2021)
Influenced by culture war theories first introduced in the 1990s, much of the recent history of modern American religion and politics is written in a mode that takes for granted the enduring partisan divides that can blind us to the complex and dynamic intersections of faith and politics. The contributors to Religion and Politics Beyond the Culture Wars argue that such narratives do not tell the whole story of religion and politics in the modern age. This collection of essays, authored by leading scholars in American religious and political history, challenges readers to look past familiar clashes over social issues to appreciate the ways in which faith has fueled twentieth-century U.S. politics beyond predictable partisan divides and across a spectrum of debates ranging from environment to labor, immigration to civil rights, domestic legislation to foreign policy. Offering fresh illustrations drawn from a range of innovative primary sources, theories, and methods, these essays emphasize that our rendering of religion and politics in the twentieth century must appreciate the intersectionality of identities, interests, and motivations that transpire and exist outside an unbending dualistic paradigm. Contributors: Darren Dochuk, Janine Giordano Drake, Joseph Kip Kosek, Josef Sorett, Patrick Q. Mason, Wendy L. Wall, Mark Brilliant, Andrew Preston, Matthew Avery Sutton, Kathleen Sprows Cummings, Benjamin Francis-Fallon, Michelle Nickerson, Keith Makoto Woodhouse, Kate Bowler, and James T. Kloppenberg.